On Winged Wheels to the Opatija Riviera - Mirjana Kos; Miljenko Lapaine (Kartografija i Geoinformacije, 2018)
The exhibition On Winged Wheels to the Opatija Riviera is dedicated to two important anniversaries: the establishment of the railway lines and the introduction of the Opatija tram line. It includes many artefacts and historical facts about the railways and trams – a map of rail and postal connections, photographs of the railway construction, commemorative postage stamps, original blueprints of the railway stations, a sketch of the tram line, a brake from an Opatija tram, and photographs of tram workers and passengers on the last ride before the tram was taken out of use in 1933. The authors of the exhibition are Mirjana Kos and Jan-Bernd Urban.